Evidence for food-related and non-food-related maladaptive preference in a mouse model of binge eating disorder - Vajdová, Daniela; Ježková, Janet; Procházková, Petra; Roubalová, Radka; Patrono, Enrico (Frontiers in Behavioral Neuroscience, 2025)
IntroductionRising numbers of binge eating disorder (BED) cases and excessive associated economic costs, together with the absence of efficient treatment strategies, highlight the importance of research in this area. To date, numerous studies have investigated the role of aberrant motivation in compulsive, maladaptive feeding behaviors. However, other aspects of maladaptive preference toward foods, possibly involving risk-based decision-making processes, are not yet fully elucidated.MethodsIn this research, two types of environmental stressors—food-related and non-food-related—are explored in their ability to model compulsive behavior toward palatable food in mice.Results and discussionResults from the behavioral experiments suggest that both types of stressors, when paired with the availability of highly palatable food, can produce aberrant motivation toward such food. These findings were subsequently supported by data obtained from cortisol concentration analysis in subjects.